Tārikh al-Ma’had al-Turāthī wa Thaqafātuhu - Mas'ud, Abdurrahman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
Within the Indonesian context, the history of pesantren cannot be alienated from that of Walisongo (The Nine Saint), who were said to be responsible for the spread of Islam in Java in the 16th-17th centuries. Maulana Malik Ibrahim (died 1419), the